Experimental democracy for China: Dewey’s method - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2018)
This chapter explores the relevance of Dewey’s philosophy of democracy for China within the context of Dewey’s historical visit to China (1919–1921) and continuing debates about his influence among the Chinese. Dewey’s pragmatism illuminates certain problems in the contemporary discourses about China’s democratization, including questions whether Chinese culture is an obstacle to democratization and the strengths of a Deweyan approach to articulating a Confucian democracy that could work in China. Dewey’s emphasis on experimentation in social reforms and his fallibilism regarding the political institutions of democracy open up new possibilities for China’s democratization and suggest where one might look to discover the indigenous conditions—the varied experiments being conducted in local governance and civil society—from which a Chinese democracy might be born.